Empowerment of Women Through Jasmine (Jasminum sambac) Cultivation - Sharmila Bharathi C, B Mohan, S Alagudurai, R Sangeetha, G Gohila and K Paneerselvam (Journal of Krishi Vigyan, 2015)
Krishi Vigyan Kendra, Namakkal popularized jasmine ( Jasminum sambac ) cultivation. For this,7,660 three months old rooted cuttings of jasmine variety Ramanathapuram Gundu malligai was supplied to twelve farm women covering an area of 1.66 ha. as a sustainable livelihood income generating activity to mitigate poverty. Jasmine being a hardy crop withstood drought, long dry spells and survived to yield flowers throughout the year and was a perennial source of income (average profit Rs.40000/ 0.08 ha. / year) that helped sustaining interest of the farm women. The income from jasmine cultivation improved the quality of life, mainly health of the farm family and also helped them to build their asset base by repairing of home and vehicles etc